Population and distribution of Rekrekan(Presbytis fredericae ) in the Southern Slope of Mt.Slamet - ARIF SETIAWAN; DJUWANTOKO DJUWANTOKO; A. W. BINTARI (Biodiversitas Journal of Biological Diversity, 2007)
Javan fuscous leaf monkey (Presbytis fredericee Sady,1930)is one of an endemic and endangered leaf eating monkeys that still exist and living in several patchy forests In Central of Java. Survey of this monkeyswas done in the Southern section slope of Mount Siamet areas (36, 6559 km2). Central Java, Indonesia. Direct observation methods using distance sampling was applied to estimate the population number of these monkeys. The survey was conducted during dry season, on May to June. 2005. Result of the population estimation size using DISTANCE 5.0 computer program within uniform key and hermite polynomial adjustment was 219 Individuals, and population densitywas estimated around 5.96 Indlvldual/km2(CV = 75.72%;95%CI = 1.2466- 28.532).@2007 Jurusan BiolO9IFMIPA UNS SurakartaKeywords: (Presbytis fredericae), populationand distribution,Mt.Slamet Indonesia